Compact UWB microstrip antenna with quadruple band-notched characteristics for short distance wireless tele-communication applications - Rayavaram, Kalyan; Reddy, K.T.V; Kesari, Padma Priya (International Journal of Engineering and Technology, 2018)
In this paper, the design and simulation of a compact ultra-wide band (UWB) microstrip antenna with quadruple band-notched characteristics for short-distance wireless telecommunication applications were explored. The design process of the antenna is carried on FR4 substrate with dielectric constant 4.4, loss tangent 0.02, thickness of 0. 8mm and the size of the proposed antenna are 30Ã—20 mm2. The rectangular monopole antenna endures a rectangular radiating patch with chamfered bevel slots on the top side, and a defective ground planed on the bottom side of the substrate. To realize single, dual, triple and quadruple band notch characteristics, slot-1 is created on the patch to achieve first notch at 3.5 GHz, which eliminates WIMAX signal, slot-2 is created on the patch to achieve second notch at 4.6 GHz, which eliminates INSAT signal, slot-3 is created on the patch to achieve third notch at 5.5 GHz, which eliminates WLAN signal and also fourth notch is created at 9.5GHz which eliminates X-band frequency with slot-1 outer length. The proposed antenna is well miniaturized and can be easily integrated with any compact devices. The simulated result shows that proposed antenna gain a good range of UWB from (2.6 GHz to 13.4 GHz).